Identification of scintillation signatures on GPS signals originating from plasma structures detected with EISCAT incoherent scatter radar along the same line of sight. Issue 1 (13th January 2017) - Forte, Biagio; Coleman, Chris; Skone, Susan; Häggström, Ingemar; Mitchell, Cathryn; Da Dalt, Federico; Panicciari, Tommaso; Kinrade, Joe; Bust, Gary
Abstract: Ionospheric scintillation originates from the scattering of electromagnetic waves through spatial gradients in the plasma density distribution, drifting across a given propagation direction. Ionospheric scintillation represents a disruptive manifestation of adverse space weather conditions through degradation of the reliability and continuity of satellite telecommunication and navigation systems and services (e.g., European Geostationary Navigation Overlay Service, EGNOS). The purpose of the experiment presented here was to determine the contribution of auroral ionization structures to GPS scintillation. European Incoherent Scatter (EISCAT) measurements were obtained along the same line of sight of a given GPS satellite observed from Tromso and followed by means of the EISCAT UHF radar to causally identify plasma structures that give rise to scintillation on the co‐aligned GPS radio link. Large‐scale structures associated with the poleward edge of the ionospheric trough, with auroral arcs in the nightside auroral oval and with particle precipitation at the onset of a substorm were indeed identified as responsible for enhanced phase scintillation at L band. For the first time it was observed that the observed large‐scale structures did not cascade into smaller‐scale structures, leading to enhanced phase scintillation without amplitude scintillation. More measurements and theory are necessary to understand the mechanism responsible for the inhibition of large‐scale to small‐scale energy cascade and to reproduce the observations. This aspect is fundamental to model the scattering of radio waves propagating through these ionization structures. New insights from this experiment allow a better characterization of the impact that space weather can have on satellite telecommunications and navigation services. Key Points: EISCAT incoherent scatter radar beam co‐aligned with GPS satellite line of sight Absence of large‐scale to small‐scale energy cascade in the auroral E and F regions Scintillation‐inducing plasma gradients in the auroral E and F regions